Is the Trendelenburg position the only way to better visualize internal jugular veins? - Judickas, Šarūnas; Gineitytė, Dalia; Kezytė, Greta; Gaižauskas, Ernestas; Šerpytis, Mindaugas; Šipylaitė, Jūratė (Acta medica Lituanica, 2019)
Background. A larger cross-sectional area (CSA) of the internal jugular vein (IJV) makes catheterization easier and the Trendelenburg position is used to achieve this. Unfortunately, it is not comfortable for conscious patients. The aim was to evaluate the impact of alternative manoeuvres on the enlargement of the CSA of the IJV and to compare these manoeuvres with the Trendelenburg position. Materials and methods. A prospective study of 63 healthy volunteers was conducted. Two-dimensional ultrasound images of right IJV (RIJV) and left IJV (LIJV) were recorded at the level of the cricoid cartilage in the supine position with and without head rotation by 30 degrees during various manoeuvres. Results. The CSA of the RIJV and the LIJV significantly increased using hold of deep breath (mean size (cm2) RIJV 1.59 ± 0.82, LIJV 1.07 ± 0.64; both p < 0.001) and the Trendelenburg position (mean size (cm2) RIJV 1.5 ± 0.68, LIJV 0.99 ± 0.54; both p < 0.001). The 45-degree passive leg raise increased the CSA of only the RIJV (mean size (cm2) 1.17 ± 0.61, p = 0.024). These manoeuvres were compared with the Trendelenburg position. There was no significant difference in the size of the CSA using hold of deep breath on the LIJV (p = 0.08) and the RIJV (p = 0.203). The passive leg raise had a significantly weaker impact on the size of the CSA (p < 0.001 for both sides). Conclusions. Hold of deep breath and 45-degree passive leg raise (the latter limited for the right side only) are alternative manoeuvres to improve visualization of internal jugular veins for conscious patients. Hold of deep breath was as effective as the Trendelenburg position.